9c+4=13c-6

Simple and best practice solution for 9c+4=13c-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9c+4=13c-6 equation:



9c+4=13c-6
We move all terms to the left:
9c+4-(13c-6)=0
We get rid of parentheses
9c-13c+6+4=0
We add all the numbers together, and all the variables
-4c+10=0
We move all terms containing c to the left, all other terms to the right
-4c=-10
c=-10/-4
c=2+1/2

See similar equations:

| 3p+10=5p-70 | | X^2-6x+9=4√X^2-6x+6 | | 5/8x+8=-3 | | 10r-25=5r+50 | | 9w-4=12w-25 | | n2-n=80 | | 17b+3=11b+39 | | 4d–5=2d+7* | | 40.63=8g+3.51 | | 2x=+7x–6x+8 | | 16.63=3g+3.85 | | (x+3)49=90 | | 16.14=3g+3.57 | | (x+5)29=180 | | 13=1+4k | | 3x+64=2197 | | 6=1/2m | | Y=70x,X=3 | | 3n-8=8n+5 | | x=150.3x-20=130 | | Y=70xX=3 | | x=1503x-20=130 | | 2(7x+3)+90=180 | | 1/2(4y-20)=-30 | | X+2/2-2x-7/7=-1 | | 3(x+4)-12=39 | | 3(x+40-12=39 | | -2x-8=-4. | | {h}6-1=36h−1=3 | | 7x=1804 | | 7x+7=18(11) | | 42.03=9g+3.96 |

Equations solver categories